2017
DOI: 10.1021/acs.est.7b01001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Periphyton Communities Associated with Selenium Bioconcentration and Trophic Transfer in a Simple Food Chain

Abstract: A major source of uncertainty in predicting selenium (Se) distribution in aquatic food webs lies in the enrichment factor (EF), the ratio of Se bioconcentration in primary producers and microorganisms relative to the concentration of Se in the surrounding water. It has been well demonstrated that EFs can vary dramatically among individual algal taxa, but data are lacking regarding the influence of periphyton community composition on EFs for a given geochemical form of Se. Therefore, the goals of this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Despite differences between years, Se enrichment in periphyton (Table 4) from both measured (2000-89 000 L/g) and sensor-estimated TSe (2670-55 500 L/g) are in the same order of magnitude reported in previous studies and also showed an inverse proportional relationship to TSe concentrations in water (Friesen et al, 2017;Markwart et al, 2019;Muscatello & Janz, 2009). Overall, the EF results suggest that without real-time data on estimated TSe concentrations, calculated EFs based on a few grab samples could underestimate time-integrated EFs at Sites 3, 4, and 6 in 2018 and Sites 6 and 10 in 2019.…”
Section: Selenium Concentrations In Periphyton and Benthic Macroinver...supporting
confidence: 71%
“…Despite differences between years, Se enrichment in periphyton (Table 4) from both measured (2000-89 000 L/g) and sensor-estimated TSe (2670-55 500 L/g) are in the same order of magnitude reported in previous studies and also showed an inverse proportional relationship to TSe concentrations in water (Friesen et al, 2017;Markwart et al, 2019;Muscatello & Janz, 2009). Overall, the EF results suggest that without real-time data on estimated TSe concentrations, calculated EFs based on a few grab samples could underestimate time-integrated EFs at Sites 3, 4, and 6 in 2018 and Sites 6 and 10 in 2019.…”
Section: Selenium Concentrations In Periphyton and Benthic Macroinver...supporting
confidence: 71%
“…Chironomus dilutus and other Chironomidae species can reach Se equilibrium within 8 days of exposure (Franz et al, 2011), whereas pseudo–steady state took approximately 28 days in experiments with the amphipod H. azteca (Raes, 2020). A pseudo–steady state of 7 days was reported for the gastropod Stagnicola elodes , with slightly increasing Se concentrations over 21 days of exposure but not statistically different from day 7 (Friesen et al, 2017). Mayfly larvae (Heptageniidae) sampled from a mesocosms experiment seemed to have reached Se steady state before 21 days of exposure (Graves et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Still, the 2018 results might be related to other variables not investigated in the present study, such as potential temporal changes in the proportion of Se oxyanions (selenate vs. selenite) in treated diluted effluent and lake water (Gojkovic et al, 2015; Schiavon et al, 2017). In addition, factors such as the ionic competition between sulfate (Supporting Information, Tables S3 and S4) and selenate for Se uptake by periphyton (DeForest et al, 2017; Fournier et al, 2006, 2010; Ponton et al, 2020) along with potential differences in periphyton community composition among years (Chételat et al, 1999; Friesen et al, 2017; Markwart et al, 2019) could help explain the results found. In the following year, overall lower aqueous Se concentrations in McClean Lake east basin prevented saturation limits from being reached by periphyton, and Se bioconcentration was, therefore, considerably lower.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research on nutrient limitation in rivers and streams has focussed on measuring overall changes in autotrophic biomass via Chl‐ a and ash free dry mass (AFDM). Biochemical approaches such as pigment analysis (Tamm et al, 2015) and metagenomics (Bengtsson et al, 2018; Friesen et al, 2017) increasingly are being used to characterise the functional taxonomy of freshwater periphyton. Specifically, chemotaxonomy based on algal accessory pigments via high performance liquid chromatography (HPLC) is an alternative and straightforward method which is compatible with algal nutrient limitation experiments (Dalton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%